Sosialisasi Deteksi Dini Penyakit Demam Berdarah di Kelurahan Kebagusan Dengan Kit Diagnostic - Santy Handayani; Didik Nur Huda (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2025)
Dengue Hemorrhagic Fever (DHF) is a disease that is often found in Indonesia. Efforts to prevent dengue fever need to be made because this disease is quite deadly. Community service was carried out at the Kebagusan Village Office, South Jakarta, which focused on training in the use of diagnostic kits by JUMANTIK cadres, Kebagusan Village. The method of this activity is in the form of socialization, introduction and training in the use of diagnostic kits for JUMANTIK cadres. This activity was attended by JUMANTIK RT 08 RW 04 cadres thereby increasing insight and knowledge of the use of malat diagnostic kits. The use of this diagnostic kit increases the work quality of JUMANTIK cadres to prevent dengue fever.